Nurses' attitudes towards hospitalized older adults in a tertiary care setting in Ghana - Yakubu H. Yakubu; Abdul‐Ganiyu Fuseini; Eleanor Holroyd (Wiley, 2022)
Abstract Introduction The increasing population of older adults and rapid increases in co‐morbidities globally has necessitated the need for a healthcare delivery system that meets the multifaceted needs of the growing population of older adults. Concurrent with these rising complex health needs is the importance of positive, non‐judgmental attitudes of health services providers towards older adults. Moreover, this is particularly important in the nursing profession, given nurses' significant and crucial roles in healthcare settings. Aim The study aimed to evaluate nurses' attitudes towards older adults in a tertiary hospital in Ghana. Design It employed a descriptive cross‐sectional quantitative design. Method Data were collected from 160 registered adult medical and surgical ward nurses using the Ageism Attitude Scale (AAS). Results Findings indicated that more than half of the participants had a diploma in general nursing. None of the nurses surveyed specialized in the care of older adults, and the mean age of participants was 30.14 (3.75) (minimum 24 and maximum 42 years). Female nurses had more positive attitudes than their male counterparts. Although the surveyed nurses reported a somewhat positive attitude towards older adults, there was no correlation between nurses' education levels and positive attitudes.